Meta-Analysis: The Effectiveness Of Project-Based Learning Model On Learning Outcomes - Wagino Wagino; Ambiyar Ambiyar; Wakhinuddin S; Suhendar Suhendar; Iffarial Nanda (VANOS Journal of Mechanical Engineering Education, 2022)
This consider points to examine the adequacy of the project-based learning show on learning results. This consider employments a meta-analysis strategy with auxiliary information sorts. The information were gotten within the frame of post test comes about for the control lessen and the exploratory class from inquire about articles employing a venture based learning show for learning results. A add up to of 27 investigate articles were dismembered and the information gotten were calculated utilizing the impact estimate (ES) equation. The calculation results show that the project-based learning show includes a moderate effect on learning results. Hence, the project-based learning show is successful and can be utilized within the learning handle.